SPEECH STYLE OF SOPHIE DEVEROUX IN TV SERIES â€œLEVERAGEâ€ - DWI RAMADHAN, BAGUS (LANGUAGE HORIZON, 2018)
Abstract Language has developed in society and causes the existence of language variations. One of them is speech style which deals with the level of formality based on the situations, condition and need of speech event. Generally, someone speaks formally to the person who has just been known, older or higher status. In this study the character that being analysed was Sophie Deveroux. She is the main focus in this study. Hence, the writer intends to analyse 1) What kinds of speech style are used by Sophie Deveroux in the TV series “Leverage” and 2) Why does Sophie Deveroux use certain types of speech style in the TV series “Leverage”. This study was conducted by using qualitative method and Speech theory proposed by Dell Hymes where the setting and scene, participants, ends, act sequences, key, instrumentalities, norms of interaction and interpretation, and genre are considered to determine someone speech style. Then, the result gotten from this study shows that are 8 data of formal style, 6 data of consultative style, 14 data of casual style and 17 data of intimate style. There is no frozen style found in the TV series. Formal style does not always happen in a formal place or vice versa. This happened on all of the speech style aspects in this study. Keywords: speech style, speech situation, TV series, Leverage   Abstrak Bahasa telah berkembang di masyarakat dan menyebabkan adanya variasi bahasa. Salah satunya adalah gaya bicara yang berkaitan dengan tingkat formalitas berdasarkan situasi, kondisi dan kebutuhan tertentu. Umumnya, seseorang berbicara secara formal kepada orang yang baru dikenal, statusnya lebih tua atau lebih tinggi status sosialnya. Dalam penelitian ini karakter yang dianalisis adalah Sophie Deveroux. Dia adalah fokus utama dalam penelitian ini. Oleh karena itu, penulis bermaksud untuk menganalisis 1) Gaya bicara seperti apa yang digunakan oleh Sophie Deveroux dalam serial TV